Development and Validation of a Gene Signature for Prediction of Relapse in Stage I Testicular Germ Cell Tumors - Zhou, Jian-Guo; Yang, Jie; Jin, Su-Han; Xiao, Siyu; Shi, Lei; Zhang, Ting-You; Ma, Hu; Gaipl, Udo S. (Frontiers in Oncology, 2020)
Background: Testicular germ cell tumors (TGCTs) are commonly diagnosed tumors in young men. However, a satisfactory approach to predict relapse of stage I TGCTs is still lack. Therefore, this study aimed to develop a robust risk score model for stage I TGCTs. Method: RNA-sequence data of stage I TGCTs and normal testis samples were downloaded and analyzed to identify different expression genes. Gene based prognostic model was constructed in The Cancer Genome Atlas (TCGA) using LASSO regression analysis and validated in GSE99420 dataset. Potential biological functions of the genes in prognostic model were determined via Gene Set Enrichment Analysis (GSEA) between high-risk and low-risk patients. Results: A total of 9391 differentially expressed genes and 84 prognosis-related genes were identified. A 8-gene-based risk score model was constructed to divide patients into high- or low-risk of relapse. The low-risk patients had a significant better RFS than high-risk's both in training and validation cohort (HR = 0.129, 95% CI = 0.059-0.284, P < 0.001; HR = 0.277, 95% CI = 0.116-0.661, P = 0.004, respectively). The AUC values at 5 years was 0.805 and 0.724 in the training and validation cohort, respectively. Functional enrichment analyses showed that DNA replication, Ribosome, Cell cycle and TGF-beta signaling pathway may contribute to the relapse process.¬ Conclusion: In summary, our analysis provided a novel 8-gene signature that could predict RFS in stage I TGCT patients.